KARAKTERISTIK GEOKIMIA DAN PETROGRAFI ORGANIK SERPIH TALANG AKAR, CEKUNGAN SUMATERA SELATAN - Novianti, Winda; Amijaya, Hendra (Departmen Teknik Geologi, 2013)
Talang Akar Formation is one of the formation that act as source rock of South Sumatera Basin which is known as a prominent oil producing basin in Indonesia. This study discuss the geochemical characteristics by means of Rock Eval Pyrolysis method and organic petrography of shale taken from outcrops of Talang Akar Formation in Lahat and Pangkalan Balai. The result of Rock Eval Pyrolysis analysis show that TOC values range from 0.94 %-4.33 %, the value of HI range from 45 -235 mgHC /g TOC , OI 4-97 mgCO2 / g TOC , vitrinite reflectance ( Ro ) 0.2%-0.48 % , and Tmax 426 0 C -440 0 C. Geochemistry data from Pangkalan Balai area show that this shale is still immature but has good potential to be source rock, with expected dominant product of gas. Whereas Lahat geochemistry data show fair potential to be source rock, oil as dominant product with level of maturity is mature. Meanwhile, based on organic petrography analysis show that both in Pangkalan Balai and Lahat area are dominated by liptinit maceral. Key words--- shale, geochemistry, Talang Akar Formation, South Sumatera